PENGARUH PERMAINAN TEBAK ASON TERHADAP PENAMBAHAN KOSA KATA BAHASA ANAK USIA 5-6 TAHUN - Emiliana Sugin; Marwadi Marwadi; Lukmanulhakim Lukmanulhakim (Universitas Tanjungpura, 2022)
AbstractThis research aims to determine the effect of the Tebak Ason game on the addition of language vocabulary for children aged 5-6 years in Mulia Dharma Kindergarten Pontianak. The research method is pre-experimental with observation and documentation. The research subjects were group B children aged 5-6 years in Mulia Dharma Kindergarten Pontianak. The results showed that the influence of the Tebak Ason game on the addition of language vocabulary for children aged 5-6 years at Mulia Dharma Kindergarten Pontianak, developed very well. The addition of language vocabulary for children aged 5-6 years at Mulia Dharma Kindergarten Pontianak before using the Tebak Ason game was still classified in the moderate criteria or starting to develop, while after using the Tebak Ason game experienced a significant difference or influence and was classified in the criteria for developing very well. Based on the results of the significant value of the paired sample t-test test of 0.000 and the effect size value of 1.868852, it can be concluded that there is a significant effect between the use of the Tebak Ason game on the addition of the language vocabulary of children aged 5-6 years at Mulia Dharma Kindergarten Pontianak.Keywords: Tebak Ason, Game, Language Vacabulary